2009
DOI: 10.1200/jco.2008.20.1301
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Resectability Using Hepatic Artery Infusion Plus Systemic Chemotherapy for the Treatment of Unresectable Liver Metastases From Colorectal Carcinoma

Abstract: PURPOSE To determine the conversion to resectability in patients with unresectable liver metastases from colorectal cancer treated with hepatic arterial infusion (HAI) plus systemic oxaliplatin and irinotecan (CPT-11). PATIENTS AND METHODS Forty-nine patients with unresectable liver metastases (53% previously treated with chemotherapy) were enrolled onto a phase I protocol with HAI floxuridine and dexamethasone plus systemic chemotherapy with oxaliplatin and irinotecan. Results Ninety-two percent of the 49 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
161
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(173 citation statements)
references
References 21 publications
(12 reference statements)
4
161
1
7
Order By: Relevance
“…HAI of chemotherapy has been used in patients with unresectable metastases confined to the liver. Kemeny et al (25) found that the combination of regional HAI floxuridine/dexamethasone and systemic oxaliplatin and irinotecan is an effective regimen for the treatment of patients with unresectable liver metastases from colorectal cancer, demonstrating a 47% conversion to resection. With laparoscopy, we successfully implanted a chemotherapy pump into the hepatic artery; meanwhile, the main lesions of the liver were administrated ethanol to induce tumor necrosis and reduce tumor burden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HAI of chemotherapy has been used in patients with unresectable metastases confined to the liver. Kemeny et al (25) found that the combination of regional HAI floxuridine/dexamethasone and systemic oxaliplatin and irinotecan is an effective regimen for the treatment of patients with unresectable liver metastases from colorectal cancer, demonstrating a 47% conversion to resection. With laparoscopy, we successfully implanted a chemotherapy pump into the hepatic artery; meanwhile, the main lesions of the liver were administrated ethanol to induce tumor necrosis and reduce tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the liver lesions resulted in fatality after the primary tumor was resected. For these patients, hepatic artery infusion (HAI) was often suggested to provide for the lesions in the liver (25). HAI of chemotherapy has been used in patients with unresectable metastases confined to the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A French group has demonstrated the prognostic similarities of PC and liver metastases in colorectal cancer when there was only one metastatic site involved [26]. Bilateral suboptimally resectable liver metastases are initially treated with hepatic intra-arterial infusion (HAIP) associated with systemic chemotherapy which offers conversion to resectability in 25-50 % of all cases [38,39]. A similar strategy in the initially unresectable PC of colorectal origin may correspond to the present protocol.…”
Section: Toxicitymentioning
confidence: 99%
“…The demographic, clinical and histological characteristics of the patients are shown in Table 1. The median PCI was 29.5 (range [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. One patient developed a recurrence of already treated PC associated with a midline parietal metastasis.…”
Section: Patient Characteristicsmentioning
confidence: 99%